GESTÃO DE RISCOS EM PROJETOS DE ENGENHARIA - Farssura, Tássia; Kikuti, Simone; Melhado, Silvio (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Most of the failure indicated in the final results of engineering projects comes from the lack of an effective analysis of the risks involved from the outset of its development. Projects are becoming more complex and complexity tends to create uncertainties involving risks that can affect time, cost, scope, and quality, thereby compromising the project outcome. Given this scenario, this article aims to give an overview of academic literature in relation to risk management, mapping and collecting the already published papers through a quantitative analysis of bibliographic data in main databases. Also the trends and behavior of the scientific production on the subject of risk management were evaluated. The proposed question for this research is: How does the academic literature has addressed risk management theme? Brazilian and international publications were considered and these were classified with the purpose of identifying which are referring to engineering projects. After this identification, risk management gaps found in these articles related to engineering projects were analyzed in order to present an analysis of the topics already explored and to propose possible approaches that are still necessary for risk management to be carried out effectively, thus contributing, for the success of the projects.